2013
DOI: 10.1007/s11605-012-2119-8
|View full text |Cite
|
Sign up to set email alerts
|

Is Routine Intraoperative Cholangiogram Necessary in the Twenty-First Century? A National View

Abstract: Introduction Intraoperative cholangiogram (IOC) can define biliary ductal anatomy. Routine IOC has been proposed previously. However, current surgeon IOC utilization practice patterns and outcomes are unclear. Methods Nationwide Inpatient Sample 2004–2009 was queried for patients with acute biliary disease undergoing cholecystectomy (CCY). Analyses only included surgeons performing ≥10 CCY/year. We dichotomized surgeons into a routine IOC group vs. selective. Outcomes included bile duct injury, complications… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 36 publications
3
33
0
2
Order By: Relevance
“…In counter argument, Polat et al .who demonstrated that in up to 12% patients findings of CBD stones during cholecystectomy were documented and recommend routine IOC to identify duct anatomy in order to reduce the incidence of CBD injury (8) . This recommendation was also supported by Ragulin-Coyne et al with similar conclusions (9) . Moreover, complications from missed gallstones, such as biliary pancreatitis can dramatically increase the cost of patient's management and hospitalization by 10 fold, as well as morbidity and mortality.…”
Section: Discussionsupporting
confidence: 74%
“…In counter argument, Polat et al .who demonstrated that in up to 12% patients findings of CBD stones during cholecystectomy were documented and recommend routine IOC to identify duct anatomy in order to reduce the incidence of CBD injury (8) . This recommendation was also supported by Ragulin-Coyne et al with similar conclusions (9) . Moreover, complications from missed gallstones, such as biliary pancreatitis can dramatically increase the cost of patient's management and hospitalization by 10 fold, as well as morbidity and mortality.…”
Section: Discussionsupporting
confidence: 74%
“…Flum et al recommended routine IOC based on cost effectiveness in terms of dollar per life-year saved from BDI [23]. On the contrary, opponents of routine IOC contend that it results in higher complication rates, cost, and rates of additional postsurgical procedures, without a proven reduction in BDI rates or mortality [24]. Also, limitations including radiation exposure, increased operative time, and technical difficulties with the procedure are real concerns for many surgeons.…”
Section: Discussionmentioning
confidence: 99%
“…This recommendation supported by the Ragulin-Coyne et al (2013), who reached similar conclusions (9). Moreover, gallstone complications, such as biliary pancreatitis and CBD injury during laparoscopic cholecystectomy can dramatically increase the cost of recurrent hospitalization by 10 fold, as well as morbidity and mortality of patients with the gallstone pathology.…”
Section: Discussion:-mentioning
confidence: 60%